Develоpment оf а thermоcаtаlytic sensоr fоr mоnitоring ethyl аlcоhоl vаpоrs in humаn exhаled аir аnd prоcess gаses - Abdurakhmonov Ergashboy; Murodova Zulfiya B.; Abdurakhmanova Zamira; Salimova Shohista (E3S Web of Conferences, 2024)
In this work, highly sensitive thermocatalytic methods and selective devices for observe the content of ethanol vapor in the air and waste industrial gas mixtures have been developed. The main indicators of the developed sensors for the determination of ethanol were assessed. The possibility of creating highly sensitive, selective sensors using measuring and compensation thermosensitive sensor elements containing catalysts of varying activity in relation to the components of complex gas-air mixtures has been experimentally confirmed. The created sensors allow the selective determination of ethanol vapor in a mixture of various gases. The scope of application of the developed sensors is environmental monitoring of atmospheric air and process gases, pre-trip and pre-shift examination of drivers, analysis in treatment rooms, clinics and clinics to accurately determine the clinical condition of patients, etc. Sensors can also be used as a means of self-monitoring.